ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN TEKNOLOGI INFORMASI DAN PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KINERJA AKUNTAN PUBLIK - TJHAI FUNG JIN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2003)
An organization continually invest a huge amount of money in the information technology (IT) with the purpose to enable its employee to use the technology effectively and efficiently. The investment urge the organizations to learn the IT and maximized its utilizations, in the end it will increase the performance of the organizations. The research use the model developed by Thompson et. al. (1991) to see the influencing factors such as social factor, affect, complexity, job fit, long-term consequences and facilitating condition to information technology utilization. Beside a research model developed by Goodhue and Thompson (1995) connecting the use of IT with performance is applied in the research. Data is collected from big five public accounting firms in Indonesia and it is used to predict the performance of the accounting firms. The data is processed using SEM in Lisrel 8.3. The research shows that the relationship is positif and significant between social and IT utilization. Meanwhile, affect does not have any significant relationship with the IT utilization. The research also shows negative relationships between complexity, job fit, long term consequences and facilitating condition to IT utilization. The research does not support the relationship between the IT utilization and individual performance. The research also fails to shows the TAM (Technology Acceptance Model) stating that the IT utilization could affect the performance.